2013
DOI: 10.5380/psi.v17i2.26431
|View full text |Cite
|
Sign up to set email alerts
|

Valores pessoais, vínculos com a carreira e comprometimento organizacional.

Abstract: Foram investigadas as relações entre valores pessoais e vínculos do indivíduo com a carreira e com a organização de trabalho. Uma amostra de 209 trabalhadores, 116 homens e 93 mulheres, de diversos segmentos do setor terciário, responderam a medidas de comprometimento organizacional afetivo, comprometimento e entrincheiramento na carreira, e o Inventário de Valores de Schwartz. Análises de regressão revelaram que valores individualistas foram preditores do comprometimento com a carreira e valores coletivistas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
0
3
0
4
Order By: Relevance
“…The author concluded that there are two closely tied pairs of meanings, which are commitment to career and the affective basis, and career entrenchment and the continuance basis. In a later study (MAGALHÃES, 2014) he found positive relationships between entrenchment and lack of independence and proactivity, possibly resulting in attachment to the material and social gains achieved, and difficulty in exploring career alternatives and facing the stress and losses inherent in possible changes. Scheible and Bastos (2014) and Scheible et al (2013) found results consistent with these studies as they investigated the relationships between entrenchment, commitment, and performance.…”
Section: Evidence Of Overlap Between Entrenchment and The Continuancementioning
confidence: 93%
“…The author concluded that there are two closely tied pairs of meanings, which are commitment to career and the affective basis, and career entrenchment and the continuance basis. In a later study (MAGALHÃES, 2014) he found positive relationships between entrenchment and lack of independence and proactivity, possibly resulting in attachment to the material and social gains achieved, and difficulty in exploring career alternatives and facing the stress and losses inherent in possible changes. Scheible and Bastos (2014) and Scheible et al (2013) found results consistent with these studies as they investigated the relationships between entrenchment, commitment, and performance.…”
Section: Evidence Of Overlap Between Entrenchment and The Continuancementioning
confidence: 93%
“…The present study achieved a more authentic sample closer to the national census description. Muthukrishna et al, (2020) also found high power distance in Brazilian samples following Schwartz (1992) explanation that places power at the core of such phenomenon in Brazil (Fernandes & Ferreira, 2009;Magalhães, 2013;Tamayo et al, 2001), emphasizing the vertical dimension. Therefore, the absence of vertical dimension was dismantled when the sampling bias was reduced (Nelson & Shavitt, 2002).…”
Section: Discussionmentioning
confidence: 81%
“…Study 1 aimed to replicate the Triandis and Gelfand (1998) original scale in both USA and Brazilian samples. We followed recommendations for cross-cultural studies 2013).…”
Section: Studymentioning
confidence: 99%
“…Nessa categoria, 12 artigos trataram da perspectiva dos funcionários, sendo que quatro se dedicaram a avaliações de valores pessoais, estudando: 1) as influências que exercem no comprometimento organizacional, bem-estar afetivo, fadiga e burnout (GOUVEIA et al, 2009); 2) a relação com o comportamento proativo (KAMIA; PORTO, 2011); 3) diferentes formas de lidar com uma operação de aquisição (ADLER; SILVA, 2013) e 4) suas relações com os vínculos com a carreira e a organização (MAGALHÃES, 2013). Seis estudos abordaram valores organizacionais, investigando: 1) suas influências nos estilos de gerenciamento a partir da percepção de funcionários com baixa escolaridade (GOSENDO; TORRES, 2010); 2) sua percepção por colaboradores de diferentes níveis hierárquicos (SILVA; SILVA, 2010); 3) sua percepção por pessoas com deficiência e a maneira de ver a deficiência no trabalho (ÁVILA--VITOR; CARVALHO-FREITAS, 2012); 4) a percepção de funcionários sobre o estímulo ou barreira à criatividade no trabalho (BEDANI, 2012); 5) a sua influência na percepção de colaboradores sobre o suporte organizacional (ESTIVALETE; ANDRADE, 2012); 6) fatores que influenciaram mudanças individuais e organizacionais percebidas por funcionários de uma organização que sofreu um processo de intervenções (NEIVA; PAZ, 2012).…”
Section: Resultsunclassified